2005
DOI: 10.1021/ac050423p
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance Imaging Measurements of the Inhibition of Shiga-like Toxin by Synthetic Multivalent Inhibitors

Abstract: A variety of new methodologies to pattern biomolecules on surfaces and to detect binding events are currently being developed for high-throughput assay applications. Carbohydrates serve as attachment sites for toxins, bacteria, and viruses. Immobilized carbohydrate units can thus be used to directly detect these agents or as a platform for inhibitor assessment. In this work, modified glycosides were patterned on gold surfaces to monitor the binding of the homopentameric B5 cell-recognition subunit of the Shiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…[46] Initially, thiobutanol was used as the surface matrix to fabricate a P k -coated chip for SPR, but the P k -AuNP aggregated on the chip surface. However, a recent report showed that the use of a short-chain methyl ethylene glycol on the AuNP surface prevented AuNP aggregation [47] and suppressed nonspecific interactions.…”
Section: Multivalent Interactions Of P K -Aunps With B-sltmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] Initially, thiobutanol was used as the surface matrix to fabricate a P k -coated chip for SPR, but the P k -AuNP aggregated on the chip surface. However, a recent report showed that the use of a short-chain methyl ethylene glycol on the AuNP surface prevented AuNP aggregation [47] and suppressed nonspecific interactions.…”
Section: Multivalent Interactions Of P K -Aunps With B-sltmentioning
confidence: 99%
“…These inhibition results by SPR indicated that 20-l-P k -AuNP served as an A C H T U N G T R E N N U N G effective probe for B-Slt; it displayed superior antagonistic A C H T U N G T R E N N U N G activity to other P k -AuNPs, and even to a decavalent starfish inhibitor. [46] The X-ray crystal structure of B-Slt showed [15] that it is composed of five monomers, each of which contains three P k -binding sites ( Figure S2). Site 3 is nearly perpendicular to the complex and thus contributes less to P k binding [17,51] compared to sites 1 and 2.…”
Section: Multivalent Interactions Of P K -Aunps With B-sltmentioning
confidence: 99%
“…For proteomics, the applications include determining protein thickness (Otsuki et al, 2005;Wilkop et al, 2004), conformational changes , and expression profiling (Usui-Aoki et al, 2005). Other diverse application areas for SPR imaging include toxin-binding inhibition in glycomics (Kanda et al, 2005), self-assembled monolayers (Pyo et al, 2005), detection of human choriogonadotropin (Piliarik et al, 2005), and fabrication of electrochemical switches (Arena et al, 2004). SPR imaging systems have evolved over the past 20 years.…”
Section: Surface Plasmon Resonance Imagingmentioning
confidence: 99%
“…The theory was later extended to interfaces of metals and anisotropic dielectric materials (Singh & Thyagarajan 1991;Mihalache et al 1994). With the current surge of interest in application of SPP-wave-based techniques for biosensing (Homola et al 1999;Abdulhalim et al 2008), imaging (Aoki et al 2005;Kanda et al 2005) and information transmission in computer chips (Maier et al 2001), the propagation of SPPs at the interface of a metal and manufactured structures such as photonic crystals is now being explored (Huang & Zhu 2007;Hassani et al 2008).…”
Section: Introductionmentioning
confidence: 99%